High impact health service interventions for attainment of UHC in Africa: A systematic review. - Humphrey Cyprian Karamagi; Araia Berhane; Solyana Ngusbrhan Kidane; Lizah Nyawira; Mary Ani-Amponsah; Loise Nyanjau; Koulthoume Maoulana; Aminata Binetou Wahebine Seydi; Jacinta Nzinga; Jean-Marie Dangou; Triphonie Nkurunziza; Geoffrey K Bisoborwa; et al. (PLOS Global Public Health)
African countries have prioritized the attainment of targets relating to Universal Health Coverage (UHC), Health Security (HSE) and Coverage of Health Determinants (CHD)to attain their health goals. Given resource constraints, it is important to prioritize implementation of health service interventions with the highest impact. This is important to be identified across age cohorts and public health functions of health promotion, disease prevention, diagnostics, curative, rehabilitative and palliative interventions. We therefore explored the published evidence on the effectiveness of existing health service interventions addressing the diseases and conditions of concern in the Africa Region, for each age cohort and the public health functions. Six public health and economic evaluation databases, reports and grey literature were searched. A total of 151 studies and 357 interventions were identified across different health program areas, public health functions and age cohorts. Of the studies, most were carried out in the African region (43.5%), on communicable diseases (50.6%), and non-communicable diseases (36.4%). Majority of interventions are domiciled in the health promotion, disease prevention and curative functions, covering all age cohorts though the elderly cohort was least represented. Neonatal and communicable conditions dominated disease burden in the early years of life and non-communicable conditions in the later years. A menu of health interventions that are most effective at averting disease and conditions of concern across life course in the African region is therefore consolidated. These represent a comprehensive evidence-based set of interventions for prioritization by decision makers to attain desired health goals. At a country level, we also identify principles for identifying priority interventions, being the targeting of higher implementation coverage of existing interventions, combining interventions across all the public health functions-not focusing on a few functions, provision of subsidies or free interventions and prioritizing early identification of high-risk populations and communities represent these principles.